Effect of a Water Soluble Organic Additive on Growth Performances, Hematological Parameters and Cost Effectiveness in Broiler Production (Progressive Agriculture, 2013)
An experiment was conducted with 144 broiler chicks (Cobb 500) from day-old to five weeks of age to investigate the efficacy of a water additive in broiler production. The chicks were randomly distributed into four different treatments namely T1 (control), T2 (water additive as per recommended level of the manufacturer), T3 (25% less than the recommendation) and T4 (25% more than the recommendation). Broiler growth performances and hematological parameters were studied and cost effectiveness of the application of such water additive was determined. There was an improvement in both body weight and FCR due to addition of water additive although all productive performances in birds receiving treatments showed no significant differences from the control. Among the hematological parameters, lower values were obtained for mean cell volume and mean cell hemoglobin, although only the former (mean cell volume) of the treated groups differed significantly (P